Effect of DMF addition on the phase-chemical structure of Pd-doped methyl-modified silica membrane materials calcined in air atmosphere. (19th May 2018) - Yang, Jing; Fan, Wangqing; Hou, Haiyun; Guo, Yani; Jia, Debao; Xing, Xiaoting
ABSTRACT: Pd-doped methyl-modified SiO2 membrane materials were prepared by sol-gel technique with tetraethylorthosilicate (TEOS) and methyltriethoxysilane (MTES) as silicon precursors, PdCl2 as palladium source. N, N-dimethylformamide (DMF) was used as a drying control chemical additive (DCCA). The samples were characterized by X-ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and thermogravimetric (TG)-differential thermogravimetric (DTG) measurement. The effect of DMF addition on the phase and chemical structures of Pd-doped SiO2 membrane materials calcined at 350°C was discussed. The results showed that the diffraction peaks of metallic Pd 0 and PdO appeared in the XRD curve of Pd-doped SiO2 membrane material without DMF, while only the metallic Pd 0 diffraction peak can be explicitly observed in the Pd-doped SiO2 membrane material with DMF. DMF has no significant influence on the chemical structure of Pd-doped SiO2 membrane materials but can delay the oxidation of metallic Pd 0 to PdO in the air.